Bekam Basah Berpengaruh terhadap Penurunan Kadar Kolesterol Total - Muhammad Hadi Sulhan; Tantri Puspita Tantri Puspita; Mamay Mamay; Gina Nafsa Mutmainna Gina Nafsa Mutmainna (LPPM STIKES Mataram, 2024)
Abstract Introduction: Wet cupping is known to significantly lower total cholesterol, low-density lipoprotein (LDL)/high-density lipoprotein (HDL) ratio. Objective: To determine the effect of wet cupping therapy on reducing total cholesterol levels. Method: The research method used is a quasiexperiment with purposive sampling. Results: The results showed a significant effect of wet cupping therapy on total cholesterol levels.. Conclusion: Wet cupping therapy affects the decrease in total cholesterol levels.